2019
DOI: 10.1016/j.jtcme.2017.10.004
|View full text |Cite|
|
Sign up to set email alerts
|

Antidiabetic potential of Asparagus racemosus Willd leaf extracts through inhibition of α-amylase and α-glucosidase

Abstract: The aim of this work was to evaluate the inhibitory activities of different extracts of Asparagus racemosus Willd on α - amylase and α - glucosidase at varying concentrations. Diabetes mellitus is a clinical condition characterized by hyperglycaemia in which an elevated amount of glucose circulates in the blood plasma. α - amylase and α - glucosidase inhibitors are used to achieve greater control over hyperglycemia in type 2 diabetes mellitus. This study is to treat the diabetes using natural resources. We aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…The higher inhibitory activity of the α-amylase observed using hexane extract has been reported in several other studies from different plants ( Vadivelan et al., 2019 ). The inhibition activity of α-amylase inhibition using different extracts of Asparagus racemosus Willd have been reported.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The higher inhibitory activity of the α-amylase observed using hexane extract has been reported in several other studies from different plants ( Vadivelan et al., 2019 ). The inhibition activity of α-amylase inhibition using different extracts of Asparagus racemosus Willd have been reported.…”
Section: Resultssupporting
confidence: 71%
“…In their study, Acarbose still showed the highest inhibition of α-amylase. These researchers attributed the potential of anti-diabetic activity of this herb several active phytochemicals ranging from terpenes and flavonoids among many other, though at this point it cannot be clear ( Vadivelan et al., 2019 ). The current study equally showed that the leaves of E. Japonica, are potential inhibitors of α-amylase and thus can be used for T2DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Root extracts of the Asparagus racemosus exhibit α-glucosidase inhibitory activity lower than acarbose. The major active components of the extract are flavonoids, tannins and saponins ( Vadivelan et al, 2019 ).…”
Section: Non-dietary Sources and Their Bioactive α-Glucosidase Inhibimentioning
confidence: 99%
“… 13 , 14 The mechanism of the regulation of insulin release by MC extract, observed in this study, might be explained by combination effects of antidiabetic flavonoids in the extract (such as morin and quercetin), which may prevent the progressive impairment of pancreatic α-cell function due to oxidative stress and may thus reduce the occurrence of type 2 diabetes. 15 , 16
Fig. 4 Plasma insulin concentration after daily administered with MC heartwood extract for 28 days.
…”
Section: Resultsmentioning
confidence: 99%